2014
DOI: 10.1177/1541931214581186
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a fundamental property of steering

Abstract: In this paper, a general and fundamental property of steering is demonstrated: It is shown that steering corrections generally follow bell-shaped profiles of steering rate. The finding is strongly related to what is already known about reaching movements. Also, a strong linear relationship was found between the maximum steering wheel rate and the steering wheel deflection, something that indicates a constant movement time for the correction. Furthermore, by closer examination of those corrections that cannot b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

7
3

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…However, the level of description used in Figure 2 is sufficient for assessing the impact of these components upon smooth and safe control transitions. Control (determining how rapidly, and by how much, to turn the steering wheel to produce the desired wheel angle, Benderius & Markkula, 2014) and Gaze Control (e.g. saccading to, then tracking, a waypoint on the future path then tracking this waypoint, Wann & Land, 2000;Wilkie & Wann, 2002 One characteristic of the loop shown in Figure 2 is that for steering actions to remain well-calibrated with respect to the environment, it will need to operate at a sufficiently high frequency.…”
Section: An Operational Control Loop That Reflects the Perceptual-motmentioning
confidence: 99%
“…However, the level of description used in Figure 2 is sufficient for assessing the impact of these components upon smooth and safe control transitions. Control (determining how rapidly, and by how much, to turn the steering wheel to produce the desired wheel angle, Benderius & Markkula, 2014) and Gaze Control (e.g. saccading to, then tracking, a waypoint on the future path then tracking this waypoint, Wann & Land, 2000;Wilkie & Wann, 2002 One characteristic of the loop shown in Figure 2 is that for steering actions to remain well-calibrated with respect to the environment, it will need to operate at a sufficiently high frequency.…”
Section: An Operational Control Loop That Reflects the Perceptual-motmentioning
confidence: 99%
“…Previously, it has been observed that amplitude and maximum steering rate of severe evasive maneuvers are linearly correlated (Breuer, 1998;Markkula et al, submitted), suggesting a constant maneuver duration. Recently, Benderius and Markkula (2014) have shown that this correlation exists also for routine steering adjustments. These were found to follow bell-shaped profiles of movement speed, similar to what is consistently observed in laboratory experiments on reaching (Franklin & Wolpert, 2011).…”
Section: Driving Control As a Series Of Open-loop Adjustmentsmentioning
confidence: 99%
“…6 suggest that this is due to variations in the number of smaller steering corrections needed to achieve satisfactory collision avoidance (cf. [50]). It can also be noted that the average of 0.56 s shown in Fig.…”
Section: Open Loop Avoidance Steeringmentioning
confidence: 99%